2012
DOI: 10.1007/s00404-012-2361-z
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis: a premenopausal disease? Age pattern in 42,079 patients with endometriosis

Abstract: The assumption that endometriosis is a disease of the premenopausal period and in women of reproductive age needs to be called into question, as well as the influence of estrogen in fully developed endometriosis. Due to the relatively high prevalence of the condition in patients aged over 40, physicians should consider endometriosis in cases of unclear pelvic pain in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 23 publications
4
68
0
6
Order By: Relevance
“…This is in comparison to women aged 25–34 (RR – 4.0) and 45–54 (RR - 4.5), respectively [5]. However, endometriosis is also frequently diagnosed in symptomatic post-menopausal women (incidence of 2.55%) [8]. It is possible that an increase in endometriosis can be attributed, in part, to the aging of the global population.…”
Section: Introductionmentioning
confidence: 99%
“…This is in comparison to women aged 25–34 (RR – 4.0) and 45–54 (RR - 4.5), respectively [5]. However, endometriosis is also frequently diagnosed in symptomatic post-menopausal women (incidence of 2.55%) [8]. It is possible that an increase in endometriosis can be attributed, in part, to the aging of the global population.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the teenagers included might have been the ones with most severe symptoms and more likely to have endometriosis. A recent report from Germany showed that 0.05%, 1.93% and 6.1% of patients were in 10-14, 15-19 and 20-24 year age groups respectively (Haas et al [8]). These numbers suggest that endometriosis is less likely to be diagnosed in girls under the age of 20 years, compared to older women.…”
mentioning
confidence: 96%
“…samples of women laparoscopically and/or histologically diagnosed with various reproductive pathologies, encompassing ~35% of endometriosis and another ~61% of various pathologies that affect the ovary and other upper genital tract parts. According to the Haas et al's study (9), 78.6% of our women with endometriosis fall into the premenopausal group (age, ≤40 years) and 21.4% into perimenopausal group (age, 41 to 50 years). The relationship between endometriosis and bacterial infection, that has been prompted by the high incidence of disease together with the observation of pathological lesions resembling punctate blister-like lesions (23), was not clarified until recently.…”
Section: Articlementioning
confidence: 80%